Relationship of GW/P-bodies with stress granules - Stoecklin, Georg; Kedersha, Nancy (Ten years of progress in GW/P body research, 2013)
Whereas P-bodies are intimately linked to the cytoplasmic RNA decay machinery, stress granules harbor stalled translation initiation complexes that accumulate upon stress-induced translation arrest. In this Chapter, we reflect on the relationship between P-bodies and stress granules. In mammalian cells, the two structures can be clearly distinguished from each other using specific protein or RNA markers, but they also share many proteins and mRNAs. While the formation of P-bodies and stress granules is coordinately triggered by stress, their assembly appears to be regulated independently by different pathways. Under certain types of stress, P-bodies frequently dock with stress granules, and overexpressing certain proteins that localize to both structures can cause P-body/stress granule fusion. Currently available data suggest that these self-assembling compartments are controlled by flux of mRNAs within the cytoplasm, and that their assembly mirrors the translation and degradation rates of their component mRNAs.